Virtual reality and augmented reality in Onboarding of new employees - Torres, Manuela; Carneiro, Andreia; Correira, Tiago; Costa, Daniel; Ferreira, Pedro; Figueiredo, Clara; Lopes, Liliana; Marques, António; Meirinhos, Viviana; Rodrigues, Ana Cláudia; Santos, Mariana; Seixas, Daniela; et al. (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
This paper intends to present what has been studied by the scientific community about Virtual Reality (RV) and Augmented Reality (AR) on Onboarding and what is the potentiality as an empowering tool on Onboarding processes of new employees in organizations. Onboarding encompasses a series of processes that aim to train and familiarize new employees with culture, mission, values and colleagues, thus facilitating the integration of new employees into an organization, meaning, processes that facilitate adaptation to the organization. A successful Onboarding program offers new employees resources to assimilate cultural aspects and collaborate to better adapt in new environment, thus enhancing performance. The use of new technologies in work processes and therefore in Human Resource Management and Development (HRMD) is becoming more frequent. Through its own equipment, RV/RA has as main characteristic to recreate the sensation of reality, giving a individual the possibility to integrate a three-dimensional environment by performing actions or manipulating objects while using the application. Thus, the individual can enter in a controlled virtual environment and interact with an object or person as if it was physically present.